Gestión de talento humano en el comercial créditos dajumara del cantón Babahoyo. - Contreras Barzola, Cinthya Inés (2022)
The purpose of this document is to show poor administration directly affects business development or growth, in addition to generating many disadvantages inside and outside the organizational structure, whether in its production, competitiveness, percentage of sales, among other factors. One of the most frequent problems is that the company has empirical personnel, lack of communication, training, work environment, the collaborators are not clear about the situation they are going through, which is not on the right track. The objective of the present is to analyze the causes that generate the different affectations in the Dajumara Credits commercial in relation to the management of human talent in order to identify the problems and determine possible solutions based on development and case study.